Assessing the Effectiveness of Google Forms and Microsoft Forms in English Language Evaluation - Prasetya, Rizky Eka; Sofiani , Fenti (International Journal of English and Applied Linguistics (IJEAL), 2024)
Using digital tools such as Google Forms and Microsoft Forms has transformed the landscape of English language assessment, offering features like instant feedback, multimedia integration, and automated grading. However, despite their widespread adoption, limited research has systematically compared their effectiveness across critical dimensions, including usability, engagement, and feedback quality, as well as their suitability for assessing specific language skills—reading, writing, listening, and speaking. This study aimed to fill this gap by evaluating the strengths and limitations of these platforms through a mixed-methods approach. Quantitative data were collected from surveys involving 100 students and 15 educators, while qualitative insights were derived from semi-structured interviews and thematic analysis. Statistical analyses were used to assess platform-specific performance, including paired t-tests and ANOVA. The results revealed significant differences in skill-specific effectiveness: Google Forms was better suited for reading assessments (p = 0.014) due to its simplicity and ease of use, while Microsoft Forms excelled in writing (p = 0.001) and speaking (p = 0.047) tasks, owing to its advanced features like branching logic and multimedia capabilities. Both platforms were equally effective for listening assessments, reflecting their shared strengths in multimedia support. Regarding usability, Google Forms was favoured for its mobile-friendly design, whereas Microsoft Forms offered superior customization but presented a steeper learning curve. Engagement levels were comparable, with multimedia integration and instant feedback highlighted as key motivators. Feedback quality was effective on both platforms but required further refinement for open-ended tasks. This study concluded that educators should align platform selection with the specific assessment objectives, using Google Forms for receptive skills like reading and listening and Microsoft Forms for productive tasks like writing and speaking. These findings provide practical recommendations for leveraging digital tools to enhance language assessment practices.